VACCINATION IN CHILDREN WITH DIFFERENT MANIFESTATIONS OF TUBERCULOSIS INFECTION - T.S. Drozdenko; S.M. Kharit; I.F. Dovgalyuk (Педиатрическая фармакология)
The paper presents the experience of childhood immunization with the various manifestations of tuberculosis infection inanimate (ADC-M, Pneumo 23) and live vaccines (domestic divaccine «measles–parotitis», combined vaccine Priorix). The safety and efficacy of vaccination in this group of children with positive clinical and laboratory dynamics of tuberculosis on the background of a specific treatment have been demonstrated, as well as the vaccination tactics of children registered at the TB clinic based on the results of the study have been elaborated.Key words: various manifestations of tuberculosis infection, vaccination tactics, safety, efficiency, children.